PR Activities of Automotive Companies in Relation to Online Reputation Management - Milan KUBINA; Martin MIČIAK; Oliver BUBELÍNY (Communications of International Proceedings, 2021)
Nowadays, most successful companies have started to realize that taking care of the reputation and online reputation is a necessity. Positive reputation brings several advantages, represented, e.g., by higher sales and volumes of the services provided, and the inflow of new customers. Vice versa, a negative reputation causes that customers prefer the products and services of the company’s competitors. The maintenance of reputation is now heavily being shifted into the online space. The aim of this paper is to identify the performing of PR activities in relation to the building of companies’ positive reputations. The research was conducted on selected automotive companies using the data obtained from well-known news web portals where PR articles can be published. The main finding is the fact that the Skoda company performs the greatest number of PR activities, which represents its interest in the management of online reputation. The paper emphasises that the processes of building reputation, maintaining a positive reputation, and the whole online reputation management are pivotal, and the companies should use them to build their brands and good name.
Keywords: Online Reputation Management; Reputation Management; Reputation; Public Relations.